1998
DOI: 10.1042/bj3330359
|View full text |Cite
|
Sign up to set email alerts
|

Human mitochondrial phosphoenolpyruvate carboxykinase 2 gene

Abstract: The mitochodrial (mt) phosphoenolpyruvate carboxykinase 2 (PCK2) gene was isolated by screening a human genomic library with a rat cytosolic (cy) PCK1 cDNA probe comprising sequences from exons 2-9 and by PCR amplification of human genomic DNA spanning consecutive exons with known primer pairs from mtPCK2 cDNA containing sequences from two putative neighbouring exons. The mtPCK2 gene spans approx. 10 kb and consists of ten exons and nine introns. All exon-intron junction sequences match the classical GT/AG rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 42 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…However, gluconeogenesis from pyruvate and alanine (supplied by a meal or proteolysis), is most efficiently handled by PEPCK-C which can be coordinated with a host of other hormonally regulated pathways. It has been also suggested that PEPCK-C might operate in the reverse direction from PEP to oxaloacetate by using glycolysis-generated PEP imported from the cytosol to replenish the citrate cycle [42, 43]. However, our data on fed wild-type mice overexpressing PEPCK-M did not show phenotypic alterations or changes on hepatic glycolytic or lipogenic proteins (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 50%
“…However, gluconeogenesis from pyruvate and alanine (supplied by a meal or proteolysis), is most efficiently handled by PEPCK-C which can be coordinated with a host of other hormonally regulated pathways. It has been also suggested that PEPCK-C might operate in the reverse direction from PEP to oxaloacetate by using glycolysis-generated PEP imported from the cytosol to replenish the citrate cycle [42, 43]. However, our data on fed wild-type mice overexpressing PEPCK-M did not show phenotypic alterations or changes on hepatic glycolytic or lipogenic proteins (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 50%
“…Gluconeogenesis has been demonstrated in the hepatopancreas and gills from C. granulata [12,19]. Among the vertebrates, the enzyme is expressed mainly in liver and kidney, and is located in cytosol and/or mitochondria fraction [16,20]. In the other tissues the mitochondrial PEPCK form might not have a purely gluconeogenic function, and would serve other functions similar to those in ¢broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In the other tissues the mitochondrial PEPCK form might not have a purely gluconeogenic function, and would serve other functions similar to those in ¢broblasts. Mitochondrial PEPCK might operate in the reverse direction from PEP to oxaloacetate by using glycolysis-generated PEP imported from cytosol to replenish the citrate cycle [20].…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of cytosolic P-enolpyruvate carboxykinase has been thought to be glucogenesis, and the high level of the cytosolic enzyme found in the major gluconeogenic tissues, liver and kidney, is consistent with that role. However, there has long been doubt about whether the primary role of mitochondrial P-enolpyruvate carboxykinase is to support gluconeogenesis (20). The more sensitive techniques of molecular biology have shown that G-SCS and both forms of P-enolpyruvate carboxykinase are expressed at lower levels than those found in kidney and liver in a wide array of immune, nervous, muscle, and secretory tissues.…”
Section: Table II Specific Activities Of A-scs and G-scs Inmentioning
confidence: 99%